New Strait Times, 3 March 2009 (The New Straits Times Press (M) Bhd, 2009)
Malaysia has made tremendous progress in alleviating poverty. The poverty rate was redused from 50 per cent when the country gained independence in 1957 to 1.8 per cent as of last year.